Applying modified hyperbranched polyester in hydroxyl‐terminated polyether/ammonium perchlorate/aluminium/cyclotrimethylenetrinitramine (HTPE/AP/Al/RDX) composite solid propellant. Issue 1 (14th September 2020) - Wen, Xiaomu; Chen, Keke; Sang, Chao; Yuan, Shen; Luo, Yunjun
Abstract: Composite solid propellants demand fine and stable mechanical properties, creep resistance and stress relaxation performance during their long storage and usage time. In this study, modified hyperbranched polyester (MHBPE) was prepared and introduced into HTPE/AP/Al/RDX (HTPE, hydroxyl‐terminated polyether; AP, ammonium perchlorate; RDX, cyclotrimethylenetrinitramine) solid propellant as an effective additive. The static tensile and dynamic mechanical properties of this propellant before and after the introduction of MHBPE were evaluated. The elevated interfacial interaction by using MHBPE between the binder and RDX fillers improved the toughness and elasticity of the propellant. The enhancement mechanisms were also confirmed by the influence on the fracture surface morphology of the binder which was investigated by SEM. In addition, some influence on the dynamic mechanical properties of HTPE/AP/Al/RDX propellant caused by MHBPE was investigated by dynamic mechanical analysis. The creep behaviors of the HTPE/AP/Al/RDX propellants with and without MHBPE were also investigated at different stresses and temperatures. Reduced creep strain rate and strain were obtained for the modified propellant, implying enhanced creep resistance performance. The creep properties were quantitatively evaluated using a six‐element model and the long‐term creep performance of the propellant was predicted using the time–temperature superposition principle. A creep behavior of nearly 10 6 s at 30 °C could be acquired in a short‐term experiment (800 s) at 30–70 °C. Moreover, the stress relaxation investigation of the propellants with and without MHBPE at −40 °C, 20 °C and 70 °C suggested that MHBPE/HTPE/AP/Al/RDX propellant possessed better response ability to deformation. Thus, the application of MHBPE provides an efficient route of reinforcement to enhance the creep resistance and stress relaxation properties. © 2020 Society of Chemical Industry Abstract : The application of modified hyperbranched polyester (MHBPE) to HTPE/AP/Al/RDX (HTPE, hydroxyl‐terminated polyether; AP, ammonium perchlorate; RDX, cyclotrimethylenetrinitramine) propellant significantly enhanced tensile properties, creep resistance and stress relaxation.